The Effectiveness of Group Counseling with Self-Management Techniques to Reduce Academic Procrastination in Students - Barida, Muya; Maharani, Tessa Dwi; Zulfiakansa, Salwa Desti (Education and Development Research, 2025)
Academic procrastination is a tendency to delay starting or completing academic tasks. Based on assessments and interviews with guidance and counseling teachers at SMKN 5 Yogyakarta, several students were found to have high levels of academic procrastination. This study aims to determine the effectiveness of group counseling with a cognitive behavior therapy (CBT) approach and self-management techniques in reducing academic procrastination behavior. The study used an experimental method with a pretest-posttest control group design. The subjects were 10 students selected by simple random sampling, then divided into experimental and control groups. The experimental group was given group counseling services with self-management techniques, while the control group was not given any special techniques. The research instrument was an academic procrastination scale with a reliability of 0.842. The results of the Independent Sample T-Test showed a significance value of 0.027 (p <0.05), which means that group counseling with self-management techniques is effective in reducing academic procrastination of students in Yogyakarta.